ACL Reconstruction Delay in Pediatric and Adolescent Patients Is Associated with a Progressive Increased Risk of Medial Meniscal Tears. (4th August 2021) - Kolin, David A.; Dawkins, Brody; Park, Joshua; Fabricant, Peter D.; Gilmore, Allison; Seeley, Mark; Mistovich, R. Justin
Abstract : Background: We sought to investigate the relationship between the time from an anterior cruciate ligament (ACL) tear to the surgical procedure and meniscal tears in the pediatric and adolescent population. Methods: Patients who were ⩽18 years of age and had undergone an ACL reconstruction from 2006 to 2018 were identified in a retrospective, multicenter cohort. The primary outcomes were arthroscopically confirmed medial meniscal or lateral meniscal tears specifically and, in general, if any meniscal tear was present (medial and/or lateral). A multivariable Poisson regression model was used to determine whether the time from the injury to the surgical procedure was a risk factor for subsequent meniscal injury, after controlling for sex, age, and body mass index (BMI). Multivariable Poisson regression was also used to characterize associations of age, sex, and BMI with meniscal injury. Results: In this study, 546 patients with a mean age (and standard deviation) of 15.3 ± 1.6 years were identified. For each week that the surgical procedure was delayed, there was a 2% increased risk of a medial meniscal tear (adjusted relative risk [ARR], 1.02 [95% confidence interval (CI), 1.01 to 1.03]). The weekly increase in risk of a medial meniscal injury was significant for male patients (ARR, 1.03 [95% CI, 1.01 to 1.05]), but not for female patients (ARR, 1.00 [95% CI, 0.97 to 1.04]), even though the effect modification was not significant (p = 0.24). Obese male patients had a 77.9% increased risk of medial meniscal tear for each 10-week delay (p < 0.001). The use of crutches was associated with a decreased risk of medial meniscal tears (ARR, 0.47 [95% CI, 0.34 to 0.64]). Conclusions: In pediatric and adolescent patients, the risk of meniscal injury is substantial after an ACL tear. A delay from the injury to the surgical procedure was associated with a 3% weekly increased risk of medial meniscal injury for male patients, but not for female patients. The increased risk of medial meniscal injury with delays to the surgical procedure was particularly high for obese male patients. Level of Evidence: Prognostic Level IV . See Instructions for Authors for a complete description of levels of evidence.